Analysis of Government Collaborative Action on Covid-19 Disaster Management in Lampung Province - Simon Sumanjoyo Hutagalung; Eko Budi Sulistio (Iapa Proceedings Conference, 2020)
Anticipation act in disaster management is important, including non-natural disasters such as the COVID-19 pandemic. This research aims to examine the government colaborative action in dealing with covid-19 non-natural disasters in Lampung Province. This research is an experiment study, using pretes-post design methods with group control. The population in this study was 84 people from stakeholders in regional disaster management, the group was divided into 2 groups: groups that intervened through model and groups that intervened with disaster relief without model. The sample of the study results is carried out with representative criteria and relevant criteria. In this study a large sample based on that criterion was 70 people who were divided into 2 groups. The instrument used is a questionnaire. Based on the results of the known paired t test there is a difference between the pretest and postest values in each group namely the experiment group (p=0,001) and the control (p=0,001), based on the t test based on the value of the p=0.006 result, which means there is a difference in disaster management knowledge in the significant stakeholder group between the post test group I and the control group.